Social Security and Inequality in Belgium - Giulia Klinges; Alain Jousten; Mathieu Lefèbvre (Institute of Labor Economics (IZA), 2024)
Over the years, the Belgian social security system has undergone substantial reform with a prime focus on increasing older worker labor force participation. The paper explores the effect of past reforms on inequality in old age. We distinguish two separate effects: The mechanical effect considers the change in inequality and expected benefit levels due to the reforms for a fixed retirement age distribution. The behavioral effect accounts for the endogenous change caused by changes in the incentives to work. Our results show that mechanically, reforms have led to losses in expected benefits for all but the lowest income quintile. Behavioral changes had a positive but orders of magnitude smaller effect. Overall, inequality decreased as a result of reforms.
Keywords: D63; H55; I38; J26; 330; social security and public pensions; old-age labor supply; retirement; pension reforms; inequality